MITOS OHEE SUKU SENTANI, PAPUA (DALAM KAJIAN STRUKTURAL LEVI-STRAUSS) - Ummu Fatimah Ria Lestari (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This research discusses about Sentani myth “Ohee” based on Levi-Strauss’ structuralism theory. Its problem is how about structure of Sentani myth “Ohee”. This research used qualitative method. The goals of this research are to show, to describe, and to analyze Sentani myth “Ohee” based on Levi-Strauss’ structuralism theory. In its applying, data was collected by documentation technique. Then, the data was analyzed by Levi-Strauss’ methods and techniques. The results of this research were found 12 mythemes or cerithemes on that myth. Then, they were classified on five episode of text. In added, this research were found relevancy between text and the social context of Sentani people. We can look about their leadership, home living, feminism consept, mentality of Sentani people have being on Ohee myth. This research was shown that Levi-Strauss theory can be applied in the study of Sentani myth in Papua, Indonesia.